Can Swedish beef production become profitable by learning from Canadian beef production? - Nyman, Sofia (2009)
To make Swedish beef production more profitable and sustainable, even without subsidies, there is a need to find alternative production systems to reduce the cost of production. One way to find cheaper solutions for Swedish beef production is to learn from beef producers in other countries and regions with similar natural conditions as Sweden. Western Canada has a good and large scale cow-calf production and finishing of calves, and Peace River Region (PRR) in British Columbia (BC) has similar natural conditions as Central Swedish Flatlands (CSF). Alberta, where most calves from PRR are finished, and PRR are used as study regions for finding cheaper beef production systems than present in Sweden. How to reduce Swedish costs are investigated by comparing PRR and CSF budgets for cow-calf operations as well as Albertan and CSF budgets for finishing beef cattle. For CSF, budgets from the Swedish University of Agricultural Science are used. One important reason for the low costs of beef production in western Canada is outdoor wintering of the cows and finishing of young cattle in open feedlots. In order to more closely study the possibilities of introducing Canadian production systems in Sweden; natural conditions, history and especially present production systems in western Canada, cow-calf operations in PRR, feedlots in Alberta and a museum were visited.